Reflective Practice as a Professional Development Tool for EFL Lecturers in Indonesian Higher Education: A Mixed-Methods Study - Jati Suryanto (Jurnal Pengembangan Profesi Guru dan Dosen, 2026)
Professional development for EFL lecturers in Indonesian higher education remains characterized by episodic, top-down training with limited evidence of sustained impact on classroom practice. Reflective practice has been theorized as a mechanism for deeper teacher learning, yet empirical evidence from non-Western tertiary contexts remains sparse. This study examined the effects of a 14-week structured reflective practice intervention on the reflective capacities of Indonesian EFL lecturers and explored how participants experienced the process as a professional development tool. An explanatory sequential mixed-methods design was employed. Forty-two EFL lecturers from three Indonesian universities completed the Reflective Practice Questionnaire (adapted from Farrell, 2021) before and after a structured intervention incorporating guided journaling, peer observation, and monthly mentoring conversations. Quantitative data were analyzed using paired t-tests. Semi-structured interviews with 12 purposefully selected participants provided qualitative depth, analyzed via reflexive thematic analysis. Quantitative findings showed statistically significant gains in overall reflective practice scores (t(41) = 6.34, p < .001, d = 0.89), with the largest improvements in the dimensions of cognitive reflection and critical reflection. Qualitative analysis generated three themes: (1) structured scaffolding as a bridge to authentic reflection, (2) the emotional labor of unsettling routine practice, and (3) institutional constraints on sustained reflective engagement. Structured reflective practice interventions can meaningfully enhance EFL lecturers' reflective capacities when embedded within institutional support systems. However, without attention to workload and departmental culture, gains may not be sustained. Implications for CPD policy and future research are discussed.